(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This research looks at how farmers in Madhya Pradesh and Rajasthan have adapted to climate change and how it has affected their agricultural output. The research evaluated the impact of climate change on three potato cultivars Kufri Badshah, Kufri Jyoti, and Kufri Pukhraj across 38 districts in Madhya Pradesh using the WOFOST agricultural growth simulation model. Results indicate a significant decline in yield by 2055 under projected climate scenarios. In Rajasthan, analysis of historical data revealed region-specific declines in both kharif and rabi crop productivity. Farmer surveys in Bikaner showed that many are changing their farming methods, like planting at different times (87%), using different types of crops (86%), and using more water for irrigation (83%), mainly because they believe it will help their finances. The findings underscore the urgency of developing climate-resilient agricultural systems and informed policy interventions tailored to local conditions.